2010
DOI: 10.2503/jjshs1.79.56
|View full text |Cite
|
Sign up to set email alerts
|

Mapping for Axillary Shooting, Flowering Date, Primary Axis Length, and Number of Leaves in Pepper (Capsicum annuum)

Abstract: A quantitative trait locus (QTL) analysis of pepper growth traits was performed using a doubled haploid (DH) population derived from a cross between two Capsicum annuum genotypes, a bell-type cultivar 'California Wonder' and a Malaysian small-fruited cultivar 'LS2341'. Simple sequence repeats and amplified fragment length polymorphism markers were used to construct a genetic map for this population. The map spans 1,213 cM, and consists of 15 linkage groups (LGs). The axillary shooting, flowering date, primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 24 publications
(31 reference statements)
2
24
0
Order By: Relevance
“…A limited number of studies have identified QTL associated with vegetative parts of the plant (leaves, stem internodes, and petioles) (Barchi et al, M.M. Moulin et al 2009;Mimura et al, 2010). Lee et al (2011) located a QTL related to the pepper fruit length, located in linkage group 3, which explained 27% of trait phenotypic variation.…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies have identified QTL associated with vegetative parts of the plant (leaves, stem internodes, and petioles) (Barchi et al, M.M. Moulin et al 2009;Mimura et al, 2010). Lee et al (2011) located a QTL related to the pepper fruit length, located in linkage group 3, which explained 27% of trait phenotypic variation.…”
Section: Introductionmentioning
confidence: 99%
“…In all four environments, traits were highly heritable (mean 0.86 with range from 0.43 -0.96); hence good possibilities for mapping QTLs governing these traits. Our estimates of heritability are generally comparable with earlier results from Barchi et al (2009) and Mimura et al (2010) for related traits such as Axl, NLE and INL. We estimated higher heritabilities for NF and DWF as compared to result of Rao et al (2003).…”
Section: Linkage Groupsupporting
confidence: 89%
“…QTLs for fruit yield (DWF) found on LG 2 and 4 were picked up in most of the studies that evaluated fruit yield. The detected QTL for Axl on LG 3 in this study was also found in the study of Mimura et al (2010), Alimi et al (2010), Barchi et al (2009) andBen Chaim et al (2001b). Some QTLs were only picked up in some of the studies possibly due to any of the factors listed above including lack of segregation in that particular population and/or population size.…”
Section: Linkage Groupsupporting
confidence: 83%
See 2 more Smart Citations